2021
DOI: 10.1038/s41586-021-03841-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and stable mobilization of CD8+ T cells by SARS-CoV-2 mRNA vaccine

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
296
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(325 citation statements)
references
References 26 publications
25
296
2
2
Order By: Relevance
“…Several panels of pMHC tetramers were generated using previously published spike epitopes 15,32,3436 . Combinatorial tetramer staining ( Supplemental Table 2 ) and enrichment were performed as previously described 26,37 . Spike-specific CD8+ T cells identified by tetramer enrichment were subsequently assessed for memory status by CCR7 and CD45RA expression ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Several panels of pMHC tetramers were generated using previously published spike epitopes 15,32,3436 . Combinatorial tetramer staining ( Supplemental Table 2 ) and enrichment were performed as previously described 26,37 . Spike-specific CD8+ T cells identified by tetramer enrichment were subsequently assessed for memory status by CCR7 and CD45RA expression ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is the focus on humoral immunity without data on cellular immunity. It is also possible that individuals without detectable neutralizing antibodies are protected from infection or at least from severe COVID-19 by a cellular immune response [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have demonstrated that S protein-specific CD8 + T effector cells were detected already only one week after vaccination. Furthermore, CD4 + T helper and memory cells, which ensure long-term protection could be detected up to six months later [93][94][95][96][97][98][99].…”
Section: Mrna Vaccinesmentioning
confidence: 99%